The Necessity to Learn Ayurveda in the Posterity - Dhanya T; Sarath S (PT FORMOSA CENDEKIA GLOBAL, 2022)
Ayurveda took its origin in India 3000 years ago and it developed significantly during the Vedic period. In Ayurvedic treatises, the Vata, the Pitta, and the Kapha are described as three elemental doshas. The disturbance in their balance causes diseases, and maintaining them in balance is the way to prevent disease. Bringing back the doshas to balance is the treatment method in Ayurveda. So, there is a treatment for all diseases. By the principle of Trividhabhodhya sangraha, we can diagnose and do treatment of disease that was not known to us. For Example, Covid-19 which was unknown to us before. Ayurveda emphasizes the role of a healthy diet, a positive lifestyle, and nutraceutical medication. Ayurveda seems to adopt a positive holistic approach in contrast to the reductionistic approach of western modern science. As new diseases are popping up daily, Ayurveda has become a boon to mankind.